Design of broadband transimpedance amplifier for optical communication systems. Issue 8 (August 2015) - Seifouri, Mahmood; Amiri, Parviz; Rakide, Majid
Abstract This paper describes the design and analysis of broadband transimpedance amplifiers (TIAs) based on Regulated Cascode (RGC) configuration. The focus is to deal with bandwidth restriction occurring in optical receivers coming from TIA input parasitic capacitances. Despite the conventional method for broadband RGC TIA design that a ladder matching network is employed to isolate the input capacitance of TIA and the photodiode capacitance, the proposed TIA eliminates the effects of these parasitic components by absorbing them in a T-matching network. The conventional broadband RGC TIA is analyzed and the disadvantages of the ladder matching network is demonstrated in a TIA design example. The proposed RGC TIA is simulated on 0.18-μm standard RF CMOS process. The simulation results presented show that the Gain-Bandwidth product (GBW) is extended by a larger factor compared to that of the conventional broadband RGC TIA while the biasing conditions and the value of the photodiode capacitance are considered the same.